Pengaruh Kualitas Implementasi Model Pembelajaran Tipe Student Teams Achievements Divisions (STAD) dan Model Pembelajaran Tipe Numbered Head Together (NHT) terhadap Hasil Belajar Siswa Kelas X Program Keahlian Teknik Komputer dan Informatika Mata Pelajara - Duwi Ajeng Intan Sari; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The problem in class X SMK Negeri 5 Malang is the lack of student synergy when learning takes place, also the results of learning knowledge have not experienced a significant increase. The Numbered Head Together (NHT) type of learning model has not been able to increase student enthusiasm and grades. The use of other learning model variations is useful for overcoming problems that occur. The purpose of this research is to find out the different effects on the application of Student Teams Achievement Division learning models compared to NHT. The method uses Quasi Experiment method or quasi-experimental using the None-Equivalent Control Group research design. The instrument used is in the form of written test questions. The results of normality test data found abnormal data, the researchers used nonparameteric statistical tests. Hypothesis testing using the Man Whitney and Wilcoxon test method as an alternative t test was performed using SPSS software. The results give the conclusion that both models have a role in increasing learning outcomes. Using the STAD model produces a higher average learning outcomes with a value of 86.56 than the Numbered Head Together learning model has an average of 77.88. Because the two models have differences, the difference seen in STAD applies a point and reward that is useful to provide stimulus and motivation to students.